2021
DOI: 10.3389/fpsyt.2021.642403
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Interventions to Treat Antipsychotic-Induced Dyslipidemia in Schizophrenia Patients: A Systematic Review and Meta Analysis

Abstract: Introduction: Antipsychotic-induced dyslipidemia represents a common adverse effect faced by patients with schizophrenia that increases risk for developing further metabolic complications and cardiovascular disease. Despite its burden, antipsychotic-induced dyslipidemia is often left untreated, and the effectiveness of pharmacological interventions for mitigating dyslipidemia has not been well-addressed. This review aims to assess the effectiveness of pharmacological interventions in alleviating dyslipidemia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 81 publications
1
13
0
4
Order By: Relevance
“…Metformin has additionally been associated with adaptive changes in insulin sensitivity 18,[33][34][35][36] and lipid parameters such as triglycerides and total cholesterol, 20 which we also demonstrate in the present naturalistic cohort study. These findings are expected given the known antihyperglycemic properties of metformin and its use as a first-line antidiabetic agent for over five decades.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Metformin has additionally been associated with adaptive changes in insulin sensitivity 18,[33][34][35][36] and lipid parameters such as triglycerides and total cholesterol, 20 which we also demonstrate in the present naturalistic cohort study. These findings are expected given the known antihyperglycemic properties of metformin and its use as a first-line antidiabetic agent for over five decades.…”
Section: Discussionsupporting
confidence: 84%
“…In severe mental illness, metformin has been widely studied “off‐label” as a pharmacological intervention for the treatment of AP‐related weight gain, with the most evidence supporting its efficacy and safety 18,19 . Importantly, the reporting literature demonstrates good tolerability with no significant difference in reports of nausea compared with placebo, and no concerns of changes in psychiatric symptomatology 16,20 . As such, metformin is now recommended in several guidelines, including the World Health Organization (WHO) and British Association of Psychopharmacology (BAP) as well as the Mental Health section of the Canadian Obesity Guidelines, for the treatment of AP‐induced weight gain in conjunction with lifestyle modification 21–23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjunctive rosuvastatin improved the efficacy of olanzapine on behavioral impairment and hippocampal metabolic abnormalities in isolation-reared male rats [63]. Rosuvastatin also improved antipsychotic-induced dyslipidemia in patients with schizophrenia [63,64]. In consideration of the high prevalence of metabolic syndrome that includes overweight, obesity, and hyperlipidemia in schizophrenia patients, rosuvastatin might bring multiple benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses showed that metformin was well-tolerated and significantly reduced weight compared to placebo in participants with schizophrenia, schizoaffective disorder and bipolar disorder (À3.27 to À2.01 kg). 12,[29][30][31][32][33][34][35][36] Few studies have examined the role of metformin in the prevention of AiWG. A recent retrospective cohort study included in this current issue showed that metformin was associated with less weight gain compared to the control group after 6 (À0.15 kg vs. 2.99 kg) and 12 months (À0.67 kg vs. 4.72 kg) in 396 participants newly initiated on clozapine, of which 69 were on metformin ≤3 months after clozapine initiation.…”
mentioning
confidence: 99%